Credit default swap and Japanese Government Bond markets under negative interest rate policy. Issue 2 (7th March 2022) - Ito, Takayasu
Abstract: Structural changes have taken place in the markets of credit default swap (CDS) and Japanese Government Bond (JGB) after the Bank of Japan (BOJ) introduced yield curve control (YCC) under a negative interest rate policy. CDS and JGB markets were segmented before the introduction of YCC. Whether CDS markets function as insurance against the JGB market or cannot be confirmed because no causalities were found between CDS and JGB markets. However, they are integrated under a negative interest rate policy with YCC. The CDS market does not function as insurance because unilateral causalities from CDS to JGB markets were found. The purpose of YCC's introduction was an upward adjustment of the yield curve because the flattening of the yield curve damaged bank profits. A positive yield in a 10‐year JGB has become an incentive to investors. The markets of CDS and JGB have started to be integrated because JGB has regained a market and price discovery function with the introduction of YCC.